2021
DOI: 10.1111/ijcp.14934
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of the Nutritional Risk Screening System 2002 (NRS‐2002) in COVID‐19 patients admitted to the intensive care unit

Abstract: Background Nutritional status of patients with COVID‐19 can affect the recovery process of patients; however, no nutritional scale was introduced to evaluate the nutritional status of the patients. Thus, the main objective of this study was to examine the usefulness of Nutritional status‐2002 (NRS‐2002) among COVID‐19 patients admitted to the intensive care unit (ICU). Material and Methods In this cross‐sectional study, 73 patients with definitive corona diagnosis admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
5
13
0
Order By: Relevance
“…In an attempt to identify prognostic markers for COVID-19 severity and mortality, a previous study suggested a better predictive outcome when combining indicators of inflammation with those of nutritional status than that from inflammation biomarkers alone [ 31 ]. The association of malnutrition with a poor prognosis in patients with COVID-19 has been reflected in the finding of a previous study, in which patients with COVID-19 who were admitted to ICU were found to be at risk for moderate (69.9%) to severe (12.3%) malnutrition [ 12 ]. Several factors have been reported to contribute to malnutrition in patients infected with COVID-19, including elevated catabolism from fever and exertion of respiratory muscles as well as endocrinological perturbations that lead to accelerated gluconeogenesis, protein breakdown, and lipid oxidation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to identify prognostic markers for COVID-19 severity and mortality, a previous study suggested a better predictive outcome when combining indicators of inflammation with those of nutritional status than that from inflammation biomarkers alone [ 31 ]. The association of malnutrition with a poor prognosis in patients with COVID-19 has been reflected in the finding of a previous study, in which patients with COVID-19 who were admitted to ICU were found to be at risk for moderate (69.9%) to severe (12.3%) malnutrition [ 12 ]. Several factors have been reported to contribute to malnutrition in patients infected with COVID-19, including elevated catabolism from fever and exertion of respiratory muscles as well as endocrinological perturbations that lead to accelerated gluconeogenesis, protein breakdown, and lipid oxidation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other reported indicators of disease progression and mortality also included serological biomarkers such as C-reactive protein (CRP), neutrophil–lymphocyte ratio (NLR), ferritin, troponin, and lymphocyte count [ 41 , 42 ]. On the other hand, although several studies demonstrated an association between a poor nutritional status and an elevated risk of in-hospital death in patients infected with COVID-19 [ 11 , 12 ], the pooled evidence between the PNI and prognosis of COVID-19 was rarely investigated. Our finding demonstrated that a low PNI correlated with a seven-fold increased risk of mortality in hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, 78.4% of patients who died were classified as at risk of undernutrition according to NRS 2002. NRS score was associated with the risk of mortality in patients with COVID-19 in other studies [20,21]. In addition, there is scientific evidence that NRS-2002 has an excellent sensitivity in identifying patients with COVID-19 with poor clinical outcomes and is associated with length of hospitalization [22,23] and with an increased risk of loss of appetite [21e23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the NRS2002 score can be an appropriate and practical predictor of prognosis for COVID-19 patients [23,39] , an independent predictor of the clinical type of COVID-19 patients [25] , and indirectly re ecting the severity and prognosis of COVID-19 [40] . In this study, the NRS2002 score not only had a signi cant impact on disease progression and prognosis in COVID-19 patients, but also had a good predictive value for both disease severity and prognosis, with cutoff value of 0.5, 5.5, respectively.…”
mentioning
confidence: 99%